183: MOLECULAR CHARACTERIZATION OF ESOPHAGEAL ADENOCARCINOMAS (EACS) AND ITS PROGNOSTIC IMPACT. (23rd April 2022) - Houlzé-Laroye, C; Eveno, C; Buisine, M; Piessen, G; Renaud, F
Abstract: Background and aim: Esophageal adenocarcinomas (EACs) have an increasing incidence and a poor prognosis. While gastric cancer molecular subtypes are well characterized with 4 categories: EBV+, Microsatellite instability (MSI), Genomically stable (GS), Chromosomal instability (CIN), there is less data available on EACs. Often compared to stomach, recent literature only describes CIN subtype in EACs, while our clinical experience suggests greater heterogeneity. The aims of our study were (i) to characterize EACs from a molecular perspective based on a large clinico-biological database and (ii) compare our clinico-pathological data with molecular results to analyze their prognostic impact. Methods: 516 patients underwent a transthoracic esophagectomy at the University Hospital of Lille. All HES staining slides from surgical specimen was reviewed, followed by a tissue microarrays analysis. Molecular subtypes were determined by immunohistochemistry (IHC) (MMR proteins for the deficient MMR (dMMR) and MSI-PCR for the dMMR/MSI subtype, E-cadherin for the GS subtype, HER2, C-MET and KRAS for the CIN subtype), and in situ hybridization (EBV+). Results: In our series, 290 EACs are located on the esogastric junction (Siewert I and II), and 226 are above. Our current analysis highlighted one patient EBV+ and 26 dMMR status (9%). Interestingly, we observed discordances between MSI-PCR and IHC results in a third of cases (n = 8), suggesting possible modifications induced by pre-operative treatment. Our results about CIN and GS subtypes are consistent with literature with a loss of E-cadherin expression in 22 tumors (15%). An overexpression of HER2, C-MET and KRAS was noticed in 12 (8%), 41 (27%) and 13 (9%) tumors, respectively. We observed a trend toward better survival in the dMMR/MSI group comparing to GS subtype (90% vs 40% at 60 months, P = 0.07). Further analyses of the prognostic impact are in progress. Conclusion: Our study highlights the presence of biomarkers in EACs, defining at least 4 molecular subtypes, partly overlapping to those already described in gastric cancer. Interestingly, finding of EBV+ and MSI tumors was unexpected and never described elsewhere in previous genomic characterization. The prognostic impact of these 4 subtypes underlined the necessity of routine molecular characterization to adapt the therapeutic strategy.